2016
DOI: 10.1155/2016/7807921
|View full text |Cite
|
Sign up to set email alerts
|

Markedly Improved Glycemic Control in Poorly Controlled Type 2 Diabetes following Direct Acting Antiviral Treatment of Genotype 1 Hepatitis C

Abstract: Type 2 diabetes mellitus (T2DM) is often associated with hepatitis C virus (HCV) infection. Successful HCV treatment may improve glycemic control and potentially induce remission of T2DM. We report a case of an obese 52-year-old woman with mixed genotype 1a/1b HCV infection with compensated cirrhosis and a 10-year history of poorly controlled T2DM on insulin therapy. Following successful therapy with sofosbuvir, simeprevir, and ribavirin, her insulin requirements decreased and her glycosylated hemoglobin (HgA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 15 publications
2
21
0
Order By: Relevance
“…This is in agreement with several studies [12,[15][16][17]. Abdel Alem et al, found a reduction in both FBS and HbA1c after HCV eradication [18].…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with several studies [12,[15][16][17]. Abdel Alem et al, found a reduction in both FBS and HbA1c after HCV eradication [18].…”
Section: Discussionsupporting
confidence: 93%
“…(4)(5)(6)(7)(8)41) A direct causal relationship between recurrent HCV infection and onset of PTDM is supported by evidence that viral eradication leads to restoration of insulin sensitivity, improved diabetic control, and improved renal function. (19,(22)(23)(24)(25)(26)38) Restoration of insulin sensitivity has been demonstrated in nontransplant patients following HCV eradication with IFN-based therapy. (25)(26)(27)(28)(29)35) This is the first study to report the favorable effects of DAAs on PTMS in liver transplant patients with recurrent HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…(19,(22)(23)(24)(25)(26)38) Restoration of insulin sensitivity has been demonstrated in nontransplant patients following HCV eradication with IFN-based therapy. (25)(26)(27)(28)(29)35) This is the first study to report the favorable effects of DAAs on PTMS in liver transplant patients with recurrent HCV infection. The impact of viral eradication on metabolic parameters was higher among patients infected with HCV GT1 than those infected with HCV GT3 in this study, consistent with other reports, (42,43) and may reflect genotypic-specific effects on lipid profile and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are clinical case reports showing that FG and HbA1c recover after HCV eradication has been achieved [6, 7]. It has been suggested that coexisting diabetes or hyperlipidemia might interact with the response to DAAs and patients with blood glucose <126 mg/dl had a higher virologic response [8].…”
Section: Discussionmentioning
confidence: 99%